Wittgenstein and Psychoanalysis: Back to the Future of Illusion Where Freud and Wittgenstein meet without knowing it - Robert Pfaller (The European Journal of Psychoanalysis, 2014)
Apart from their apparent divergences or criticisms, Freud and Wittgenstein share at least one important point, which distinguishes them from most of the preceding philosophical tradition: they have put the role of illusion back on the philosophical agenda, which it had strangely been absent from for about 250 years. This rediscovery concerns not only people who desperately or childishly flock to an illusion like flies in a glass. It equally concerns people who are in the know, but still deal with a particular illusion, in their discourse or in their tacit practice. And finally, it concerns people who precisely by trying to be rational, fall back into illusion.